The Influence of Luxcrime Product Reviews on the Tiktok Application on Consumer Purchase Decisions in Medan City - Pohan, Marsha (Indonesian Scientific Publication, 2025)
In the digital era, social media platforms such as TikTok have become powerful channels for shaping consumer behavior, particularly in the beauty industry. This study examines the influence of Luxcrime product reviews on TikTok on consumer purchase decisions in Medan City. Using a quantitative correlational approach, data were collected through questionnaires from 100 female respondents aged 17–40 who had watched Luxcrime product review content on TikTok and had purchased the product. Data were analyzed using Spearman’s Rank Order Correlation with SPSS 29.0. The results show a significant and moderately strong relationship (ρ = 0.626, p < 0.05) between exposure to product reviews and purchase decisions, with a coefficient of determination of 39%. These findings indicate that authentic and informative TikTok reviews positively affect consumers’ decisions to purchase Luxcrime products. The study concludes that video-based e-WOM on TikTok enhances consumer trust, stimulates buying interest, and serves as an effective marketing strategy for beauty brands to optimize promotional efforts and improve sales performance.